Enhancing Engagement of Hearing-impaired Pupils in Inclusive Tanzanian Classrooms through Teaching and Learning Materials - Jane Charles Mgendi; Theodora Bali; Reuben Sungwa (Ta'dib, 2024)
Teaching and learning materials are essential tools for enhancing the engagement of hearing-impaired pupils in inclusive classrooms. This study investigated enhancing the engagement of hearing-impaired pupils in teaching and learning materials. The study employed a qualitative, phenomenological design to gain insights into the lived experiences of the participants. Forty-four participants were purposefully selected, including head teachers, teachers, hearing-impaired pupils, and hearing pupils. Data were collected through interviews and observations and analyzed thematically using Excel pivot tables. The findings indicate that hearing-impaired pupils are engaged with teaching and learning materials, such as textbooks, reference books, maps, and diagrams, through prioritizing, showing the materials, and hands-on activities. However, their engagement is hindered by limited time and communication barriers. Furthermore, most teachers reported having limited proficiency in sign language, which hinders their ability to support these pupils in the learning process. The study recommends reviewing inclusive education policies, establishing teacher training programs, and emphasizing the use of sign language as a medium of instruction for hearing-impaired pupils.┬á